GPRS performance for Maxis Operator from end-user perspective / Hanunah Othman - Othman, Hanunah (2005)
This project will study the performance of GPRS service for Maxis Operator. Three hotspot locations were identified i.e KL International Airport (KLIA), Kuala Lumpur City Centre(KLCC) and KL Sentral. These locations were chosen with assumption that there were many subscribers using GPRS service in these areas. Shah Alam was chosen as a benchmark for all other location. So the end-user will experience real performance of the GPRS services whenever they are attached to those locations. The scope of study will include Internet Browsing over GPRS, sending and receiving MMS as well as WAP browsing over GPRS. The performance of each service will be recorded such as the latency, Volume of Data for Downlink and Uplink, etc. At the end of the study, conclusion will be made whether the service is good or otherwise base on end-user experience.